Cobra II - Amr G. E. Sabet (International Institute of Islamic Thought, 2008)
This book deals with the April 2003 American invasion and occupation of Iraq. Its title comes from the code name of the military operation designed to drive toward Baghdad. The code name, in turn, was inspired by General George Patton’s 1944 military operation Cobra, during which the Allied forces broke out from Normandy to liberate France – hence Cobra II. Written in a journalistic and investigative style, it chronicles the developments and events leading to the Bush administration’s decision to attack Iraq. Described as a war of “choice” rather than of “necessity” (p. xxxi), it swiftly defeated the Iraqi army and toppled Saddam Hussein’s regime. However, it was a failure insofar as it generated a virulent insurgency that the occupyingAmerican army could not suppress. This insurgency was an unexpected by-product of the program of “transformation” espoused by former Secretary of Defense Donald Rumsfeld. As part of President George W. Bush’s vision of overhauling theAmerican military, this programbecame a sort of “official ideology” (p. 8) and response to two main concerns: (1) the long time (six months) it took to plan and amassAmerican forces during the lead-up to the 1992 GulfWar that had reversed Iraq’s invasion of Kuwait (this length of time was considered to fall short of credible “superpower” projection), and (2) the American military’s ability to fight two major wars simultaneously, which came to be known as the “two-war doctrine” (pp. 5 and 9). The problem with the second consideration was that it required large ground forces to implement the doctrine, at a time when the foreseen transformation sought to trim American forces in favor of high-tech space and precision weapons ...